The concept of rhythm in the play (Al-Academy, 2016)
The training of great importance in the play, in building optic and intellectual broadcast codes tags, and then comes after the recipient at the reception of such codes and decoded tags, and is the rhythm, the color of the most important elements of configuration, consistent with other elements, Kaltmathl, and focus, and harmony, and dissonance